PEMBERDAYAAN LITERASI EKONOMI PEREMPUAN MELALUI PELATIHAN HYDROPONIK DI KOMUNITAS BINAAN RUANG EDUKASI PENMAS [ THE EMPOWERMENT ECONOMY LITERACY WOMEN THROUGH HYDROPONIC TRAINING IN THE COMMUNITY “RUANG EDUKASI PENMAS” ] - Adi Irvansyah (Direktorat Pendidikan Masyarakat dan Pendidikan Khusus, Direktorat Jenderal PAUD, Pendidikan Dasar, dan Pendidikan Menengah, 2019)
The problem in this research is how the empowerment economic literacy of women through skills hydroponic training in “Ruang Edukasi PenMas”. Other research goal is surely to describe how the process and outcomes of women's empowerment economic literacy through skills training hydroponic in “Ruang Edukasi PenMas”. This research uses descriptive qualitative method, data collection by observation, interviews, documentation. The results of the research show that empowering women's economic literacy, as: a). the purpose of this empowerment is to empower women with certain vocational skills in the form of guided groups, b). carry out the process of empowering women's economic literacy through the stages of identifying learning needs and conducting participatory learning, c). The results of the preliminary training showed that knowledgeable participants knew about how to plant in a very limited field and participants had an entrepreneurial attitude to become hydroponic farmers. d). Evaluation of this activity is carried out through evaluation of training programs and impact evaluations. Empowerment of economic literacy through hydroponic skills training provides independence to the mentee community of “Ruang Edukasi PenMas”, namely participants are able to grow hydroponic vegetables on narrow land, and the emergence of entrepreneurial spirit by being able to sell their crops.